Abortion as disruption: discourses surrounding abortion in the talk of men - Hansjee, Jateen (Rhodes University, Faculty of Humanities, Department of Psychology, 2011)
This research examines men's talk around abortion using critical discourse analysis. Current literature indicates a dearth of studies addressing the topic of men and abortion in various domains. An understanding of men's relationship to abortion, however, is crucial to understanding abortion as a social phenomenon. This study utilises the work of Foucault around discourse and power, as well as Butler's work on gender to create a theoretical framework to approach data. Data were collected in the form of interview groups made up of men, as well as newspaper articles and on-line forum discussions that featured men as the author. What emerged from theses texts was a 'Familial Discourse' which posits the nuclear, heterosexual family as a long term relationship between a mother and father, which forms the ideal site to raise children. Discourses that support the family are a discourse of 'Equal Partnership' which establishes the man and the woman as being in a heterosexual relationship where each partner is seen to have equal power, and a discourse of 'Foetal Personhood' which constructs the foetus as a child in need of a family. Related to the heterosexual matrix, the formation of a family unit comes to be constructed as 'natural'. Abortion acts as a disruptor to these discourses. By disrupting the formation of the family unit, abortion negatively affects the individuals involved. A relationship where a formation of a family unit was disrupted cannot survive. If the female partner has an abortion without her partner, it is seen as disrupting the equal partnership between the man and the woman. Men in this case see themselves as 'powerless' compared to women. From this point a 'New Man' discourse emerges, where men position themselves as loving and responsible in the context of a nuclear, heterosexual family unit. Abortion disrupts 'Foetal Personhood' and is constructed as murder. In the case of rape the 'Familial Discourse' can be invoked either to justify abortion or resist abortion, based on whether or not a family unit can be formed. These discourses reproduce patriarchy.
Keywords: Abortion -- Psychological aspects; Abortion -- Social aspects; Men -- South Africa -- Language; Men -- South Africa -- Attitudes; Health attitudes -- South Africa; Discourse analysis -- Psychological aspects; Discourse analysis -- Social aspects